О сущности и генезисе правового нигилизма и возможностях его преодоления - Дышкант, Татьяна Николаевна (Національний юридичний університет ім. Ярослава Мудрого, 2021)
В статье акцентируется внимание на не всегда корректном использовании терминологии в литературе, посвященной проблемам права, что связано с расплывчатостью и многозначностью некоторых понятий. На этом основании уточняется значение понятия "правовой нигилизм", относимого к сфере правосознания. Обусловлена необходимость различать сущность и причины данного негативного явления, что облегчает поиск подходов к его преодолению. Проанализированы основные возможности формирования правового сознания. Выяснено, что эффективное решение данная проблема может иметь при условии анализа целого комплекса объективных причин, в основном политического и экономического характера.

The article actualizes the problem of the conceptual apparatus of legal sciences, which is associated with the vagueness and ambiguity of some concepts, including the concepts of "natural law" and "law". Ambiguity of the concept of law both as a goal and as a tool can become a source of legal conflicts. By clarifying this concept, it is possible to come to a deeper understanding of the concept of "legal nihilism", which is important for the field of law. The analysis of types of legal nihilism leads to the conclusion that it is necessary to distinguish between natural law and law, recognizing the primary role of human rights and the instrumental role of law. Two non-mutually exclusive opportunities to avoid nihilism associated with the education of citizens of legal consciousness are considered. The first is related to the education of respect for universal human values and their acceptance. Submission to the moral law, in theory, should prevent the violation of legal boundaries in the action of the subject. In the second case, this is a pragmatic way of bringing to the attention of citizens information about the inevitability of punishment. As a result, the conviction is formed that it is more profitable to comply with laws than not to comply, especially since being in the legal field ensures stability and security. The presence of prerequisites for the effective implementation of these opportunities in the modern world is analyzed. At the same time, modern realities were taken into account, for example, such as the processes of globalization and the factor of postmodernism.
On the essence and genesis of legal nihilism and the possibilities of its overcoming
Keywords: право; закон; юридический нигилизм; формирование правосознания; фактор постмодернизма; natural law; law; legal nihilism; formation of legal consciousness; factor of postmodernism